Time-domain electromagnetic fields in a cavity with temporally dispersive dielectric - Antyufeyeva, Mariya S.; Tretyakov, Oleg A. (My University, 2004)
The problem of electromagnetic field in the cavity filled with homogeneous dispersive lossy medium is considered within the frames of the evolutionary approach which involves the principle of causality [4,5]. The closed-form solution to the problem is obtained regarding constitutive relations for homogeneous dispersive lossy medium expressed in the form of differential equations. Forced oscillations in a cavity with perfectly conducting singly-connected close surface (S) of arbitrary shape are studied for the excitation by finite duration harmonic signal. © 2008 Elsevier B.V., All rights reserved.
Conference Proceedings - 10th International Conference on Mathematical Methods in Electromagnetic Theory, MMET'04 -- Dniepropetrovsk -- 64278
Keywords: Charge carriers; Current density; Dielectric materials; Differential equations; Dispersions; Eigenvalues and eigenfunctions; Electric conductivity; Electromagnetic wave polarization; Integral equations; Linearization; Matrix algebra; Maxwell equations; Molecular structure; Oscillations; Permittivity; Time domain analysis; Cavity modes; Dielectric susceptibility; Magnetic currents; Motion equation; Electromagnetic field theory